A Test of the Internal Capital Market Hypothesis - Buasook, Supannee (Asian Health, Science and Technology Reports, 2005)
Several studies found that diversification in developed capital markets, on average, did not enhance shareholders’ wealth and concluded that diversification was more likely to be an agency phenomenon rather than to improve efficiency. However, much of the literature on diversification realized the importance of internal capital markets and argued that an efficient internal capital market might create value for shareholders. This paper examined the valuation of corporate diversification in an emerging market. It followed Berger and Ofek’s methodology by computing the imputed market values. Then, two cross-sectional regression models were performed to examine the difference in market valuation between focused firms and diversified firms. Using South Korean firms, it was found that prior to the economic crisis (1994-1996) there was no difference in market valuation between focused and diversified firms. However, a significant diversification discount of 43.2 percent and 55.7 percent was found in 1997 and 1998, respectively. These findings suggested that before the crisis year the Korean capital market be segmented. Diversified firms, therefore, could take advantage from internal financing. This benefit offset the potential agency costs associated with diversification. After financial liberalization, the market has become more sophisticated. The cost differential between internal and external capital market reduced significantly whereas the agency costs still existed. Consequently, diversified firms traded at substantial discount.